PENINGKATAN KESEJAHTERAAN PEMULUNG TPST BANTAR GEBANG BEKASI MELALUI BUDIDAYA LARVA BLACK SOLDIER FLY - Hanif Aulawi; Rasyid Avicena; Uut Hanafi Rochman; Dea Damayanti; Usfa Amelia Rahma (Universitas Mataram, 2025)
The welfare of scavengers at the Bantar Gebang Integrated Waste Processing Site (TPST) in Bekasi remains a pressing issue requiring sustainable solutions. Limited income from waste collection drives the need for alternative businesses that can increase income while contributing to environmental management. This activity aims to provide scavengers with training in Black Soldier Fly (BSF) larval cultivation as a strategy to improve their economic well-being. The Participatory Action Research (PAR) approach was used, emphasizing the active involvement of scavenger groups in maggot cultivation training activities. The results of the activity indicate that BSF cultivation can reduce organic waste generation while producing economically valuable products in the form of fresh maggots, kasgot as organic fertilizer, and dried maggots. Improving scavenger skills and knowledge regarding cultivation techniques has resulted in diversified income sources, with the potential for an average increase in scavenger income of one million rupiah per month compared to conventional waste collection activities.